2020
DOI: 10.3390/ijerph17124267
|View full text |Cite
|
Sign up to set email alerts
|

Preserving Organizational Resilience, Patient Safety, and Staff Retention during COVID-19 Requires a Holistic Consideration of the Psychological Safety of Healthcare Workers

Abstract: During the COVID-19 pandemic, healthcare workers are fighting a lethal virus with acute shortages of Personal Protective Equipment (PPE). These unprecedented circumstances have amplified the sources of emotional distress and worker burnout. However, many healthcare organizations (HCOs) in the United States, have opted for a “stoic approach” to healthcare worker support, i.e., no additional support beyond federal and state policy protections for the licensing and liability of healthcare workers. In this scenari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
305
1
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(336 citation statements)
references
References 29 publications
18
305
1
12
Order By: Relevance
“…Similarly, another study reported that 63% of medical workers in Wuhan, China, demonstrated various psychopathological symptoms [ 19 ]. However, a lower prevalence of psychopathological symptoms compared to in our study was observed by the authors of the recent cross-sectional survey study based on over 4000 healthcare workers from Wuhan in which 39.1% of the study participants had psychological distress [ 20 ]. Lai et al suggested that nurses, women, frontline medical workers and those working in Wuhan, China, were more likely to report various psychopathological symptoms [ 18 ], which is consistent with our findings in the relation to female sex.…”
Section: Discussioncontrasting
confidence: 67%
“…Similarly, another study reported that 63% of medical workers in Wuhan, China, demonstrated various psychopathological symptoms [ 19 ]. However, a lower prevalence of psychopathological symptoms compared to in our study was observed by the authors of the recent cross-sectional survey study based on over 4000 healthcare workers from Wuhan in which 39.1% of the study participants had psychological distress [ 20 ]. Lai et al suggested that nurses, women, frontline medical workers and those working in Wuhan, China, were more likely to report various psychopathological symptoms [ 18 ], which is consistent with our findings in the relation to female sex.…”
Section: Discussioncontrasting
confidence: 67%
“…The 'willingness' dimension was found to be the lowest, (61.6%) reducing the overall preparedness score to 73.1%. This aligns with the literature, which underscores the importance of health worker psychological safety in serving as pre-requisites for organizational resilience (20). During normal circumstances, working in health care is recognized to be emotionally distressing (21).…”
Section: Discussionsupporting
confidence: 76%
“…Supporting employees in the workplace, listening and acting on genuine family concerns, particularly during pandemic and crisis situations, can enhance front line experiences and enable confidence in employers. Therefore, healthcare leaders need to consider how to support healthcare workers during the pandemic, to reduce emotional distress and risks staff have taken [ 34 ]. The COVID-19 pandemic has enabled many people to work remotely to prevent unnecessary cross-infection, however the lack of visibility of management has been highlighted by some [ 35 ].…”
Section: Discussionmentioning
confidence: 99%